Perancangan Interior Panti Rehabilitasi Gepeng Lansia dan Psikotik di Surabaya - Stefannie Immanuel (Intra, 2017)
The social cottage environment (LIPONSOS) is one part of the rehabilitation center that becomes one of the facility provided by the city government for homeless and beggars to be able to recover and resume socializing within the community structure. However, The LIPONSOS Keputih in Surabaya, there is a problem on the design factor so that LIPONSOS cannot maximally become a recovery container, especially for psychotic sufferers, especially elderly.In this design the author tries to finish the design by using method of design thinking. By using the concept “Alleviate by Sight” author tried to present a new understanding to give a comfortable impression that is easily accepted by psychotics so as to encourage their healing process.